Workforce planning in neurosurgery. (2nd January 2020) - Sinha, Saurabh; McKenna, Grainne; Whitfield, Peter; Thomson, Simon; Kitchen, Neil; ,
Abstract: Purpose: Since the introduction of run-through training in UK Neurosurgery in 2007, there has been no limit on the number of posts deaneries may apply for. The rationale for run-through training was based on the premise that the number of trainees recruited would match the number of consultant posts eight years later. There has been no formal survey of the number of consultant neurosurgeons in the UK for several years. A survey was undertaken to measure the current Neurosurgical workforce. Methods: The Specialist Advisory Committee undertook a survey to establish the current workforce and estimate how best to ensure that the correct number of trainees are being recruited. Data was also obtained from public bodies including the GMC, NHS Jobs and JCST. Results: Since 1993 the number of Neurosurgeons in UK and Ireland has increased from 132.5 to 389 whole time equivalents (4.4% curvilinear annual increase). The number of registered neurosurgical trainees fell 9% from 278 in 2012 to 248 in 2017. The number of UK graduates in Neurosurgical training has remained constant. The number of trainees failing to complete training has increased from 1.25 per annum in 2009–2012 to 5–6 in 2014–2017. The number of ST1 level trainees recruited has risen, which a fall in the number of trainees entering at the ST3 level has partially offset. The number of doctors with a CCT in Neurosurgery but no substantive consultant post has risen from 26 to 43 between 2015 and 2018. Conclusions: Neurosurgical workforce data should be collected regularly and a workforce planning process should be implemented. Consultant expansion is required to reduce the number of CCT holders without consultant jobs. The specialty should prevent any further increase in the number of trainees recruited and we should consider a marginal reduction in recruitment.